Analisis Gaya Bahasa dalam Kumpulan Cerita Rakyat Adonara - Maria Viviana Kewa Sua; Marselus Robot; Labu Djuli (YASIN, 2026)
Adonara folktales are an oral literary heritage containing cultural, moral, and social values passed down from generation to generation. However, studies on figurative language in Adonara folktales remain limited because previous research has focused primarily on themes and moral values. This study aims to analyze the types of figurative language and the meanings contained in a collection of Adonara folktales through a stylistic approach. The study employed a qualitative descriptive method with a stylistic approach. The data sources were the book Kumpulan Cerita Rakyat Adonara and accounts provided by informants, while the research data consisted of words, phrases, and quotations containing figurative language. The data were collected through documentation and interviews, with informants selected using purposive sampling, and were subsequently analyzed descriptively based on stylistic theory. The results showed that three folktales, namely Asal Usul Lamawolo, Asal Mula Waikebo, and Kwewa Wu’u, contained repetition, personification, symbolism, enumeration, allonym, bombast, euphemism, and metaphor, which belonged to the categories of comparative, emphatic, and contradictory figurative language. The use of these forms of figurative language serves to enhance the aesthetic presentation of the stories, clarify meanings, create atmosphere, and convey the cultural values and moral messages of the Adonara community. These findings confirm that figurative language plays an important role in strengthening aesthetic value while representing the cultural identity and local wisdom of the Adonara community. This study contributes to the development of stylistic studies on regional literature and encourages greater appreciation and preservation of folktales as part of the nation’s cultural heritage.